(untitled) (Journal of the College of Basic Education, 2022)
((And a soul and everything else, so inspire it with its immorality and piety. He who purified it has succeeded, and he who has failed it))(1) This noble verse clearly refers to the reality of the human soul in all its details and subtleties. Whoever reflects on this decisive verse will clearly see that it is rooted in the reality of the conflict between good and evil, and the dual nature of man. Since the first creation, the human world has been divided into two camps: the camp of good and the camp of evil, i. This fact is the first crime that man committed against his fellow man, when this conflict erupted in the soul of Cain, so he begged him to kill his brother Abel, and from this we are assured that the crime is a human fact and an ancient phenomenon that has been with man since his feet set foot on the earth.